Absentee Wives and Househusbands: Power, Identity and Family Dynamics - Pingol, Alice Tadeo (Review of Women's Studies; Vol 9 No 1-2 (1999): Review of Women's Studies Volume IX, Numbers 1-2 (January-December 1999))
---